Can China’s leading officials’ accountability audit of natural resources policy promote corporate emissions reduction? - Dan Yu; Kewei Hu; Yugui Hao (Carbon Management)
The Chinese government proposed the policy of the leading officials’ accountability audit of natural resources (AANR) in 2013 and launched pilot audits in some regions in 2014. In order to explore whether AANR reduces corporate environmental pollution, this paper validates the impact of AANR on corporate emission reduction using a multi-period difference-in-difference (DID) method based on a sample of Chinese A-share heavy-polluting corporations from 2010 to 2017. The results indicated that AANR can significantly reduce corporate pollutant emissions, with legitimacy pressures and resource dependence playing a mediating role. Further research found that the AANR promoted emission reduction more strongly for large-sized corporations and political connection corporations, and more significantly for corporations with higher internal and external governance levels. Policy effects were more significant in regions with favorable economic growth and legalization. The above findings verify the effect of government audits on micro corporation pollution management, enrich the theoretical system of AANR research, and provide meaningful empirical evidence for AANR's further improvement.